2009
DOI: 10.2134/agronj2009.0082
|View full text |Cite
|
Sign up to set email alerts
|

Maize Morphophysiological Responses to Intense Crowding and Low Nitrogen Availability: An Analysis and Review

Abstract: Mounting concerns over the cost and environmental impact of N fertilizer combined with progressively higher plant densities in maize (Zea mays L.) production systems make progress in maize N use efficiency (NUE) and N stress tolerance essential. The primary objectives of this 3‐yr field study were to (i) evaluate the N responsiveness, NUE, and N stress tolerance of multiple modern maize genotypes using suboptimal, optimal, and supraoptimal plant densities (54,000, 79,000, and 104,000 plants ha−1, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
195
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(236 citation statements)
references
References 114 publications
(258 reference statements)
33
195
2
6
Order By: Relevance
“…They reported considerably different profit-maximizing plant populations for the same hybrid across locations and/or seasons. For example, the profit-maximizing population of hybrid PR39W54 was 11.9 (2001), 17.5 (2002) In the research of Boomsma et al (2009), population interacted significantly with N availability, and lower populations were more suited to environments devoid of N. Over three years, per-area data gave OP(D) of 5.2 plants/m 2 for the low yielding 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 Growing season…”
Section: Implications Of Environmental Variability On Optimum Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported considerably different profit-maximizing plant populations for the same hybrid across locations and/or seasons. For example, the profit-maximizing population of hybrid PR39W54 was 11.9 (2001), 17.5 (2002) In the research of Boomsma et al (2009), population interacted significantly with N availability, and lower populations were more suited to environments devoid of N. Over three years, per-area data gave OP(D) of 5.2 plants/m 2 for the low yielding 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 Growing season…”
Section: Implications Of Environmental Variability On Optimum Populationmentioning
confidence: 99%
“…Sarlangue et al (2007) reported optimum for HI populations of 12.7 plants/m 2 for hybrid Romario that exhibited the lowest PYP, 10.6 plants/m 2 for hybrid P37P73 with an intermediate PYP, and only 6.5 plants/m 2 for the highest yielding at low population DK688. Boomsma et al (2009) discovered that strong responsiveness of grain yield per plant to reduced plant crowding accompanies higher HI values and better nitrogen use efficiency, suggesting a relatively high level of reproductive partitioning and plasticity.…”
Section: Environmental Yield Index (Eyi) and Crop Yield Potential (Cyp)mentioning
confidence: 99%
See 3 more Smart Citations